Presurgical Assessment of Patients with Refractory Temporal Lobe Epilepsy - Jaramillo, Hector; Massaro, Mónica; Ascencio, José Luis; Álvarez, Juan Felipe; Andrade, René; Zapata, José Fernando; Galeano, Luz Marina; Benjumea, Vanessa; Jaramillo, Esteban; Jiménez, Marta; Group, Refractory Epilepsy (IntechOpen, 2011)
None